Advertising and Public Relations Efficiency Measurement and Control - Zdenka Kádeková; Anton Kretter (Polityki Europejskie, Finanse i Marketing)
Public relations and advertising are important tools of marketing activities in meeting the business objectives, contributing the building of reputation and image of the enterprise and the customer´s awareness about the products. PR and advertising help to activate the customer´s interest in buying the product. Implementation of advertising and PR is a cost item for the enterprise. The amount of funds entered into advertising and PR is based on a comparison between actual and desired effect. Monitoring the efficiency of advertising and PR should be oriented primarily on measuring of microeconomic effects. Through this communicative effects in conjunction with other tools of marketing mix can be measured impact on sales (though not exactly) because the ultimate goal is obviously the economic impact of business activities.